2012
DOI: 10.1007/s12265-012-9425-0
|View full text |Cite|
|
Sign up to set email alerts
|

Early Results of Sarcomeric Gene Screening from the Egyptian National BA-HCM Program

Abstract: The present study comprised sarcomeric genotyping of the three most commonly involved sarcomeric genes: MYBPC3, MYH7, and TNNT2 in 192 unrelated Egyptian hypertrophic cardiomyopathy (HCM) index patients. Mutations were detected in 40 % of cases. Presence of positive family history was significantly (p = 0.002) associated with a higher genetic positive yield (49/78, 62.8 %). The majority of the detected mutations in the three sarcomeric genes were novel (40/62, 65 %) and mostly private (47/62, 77 %). Single nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
3
23
2
Order By: Relevance
“…Since two relatively recent reviews list known mutations until 2013 (223, 274), Table 9 includes additional mutations that were not included or identified since then, while Figure 10 indicates the total number of currently known mutations per domain.…”
Section: Myosin Binding Protein-cmentioning
confidence: 99%
“…Since two relatively recent reviews list known mutations until 2013 (223, 274), Table 9 includes additional mutations that were not included or identified since then, while Figure 10 indicates the total number of currently known mutations per domain.…”
Section: Myosin Binding Protein-cmentioning
confidence: 99%
“…Genetic causes can typically be found in 50 to 75 % of cases of hypertrophic cardiomyopathy; expanding the genetic screening analysis through increasing application of NGS technology to enable simultaneous investigation of a broad panel of inherited genes is projected to augment the genetic-positive yield [97]. In those patients in whom a mutation is identified, about 80 % involve two genes (encoding myosin heavy chain 7 and myosin-binding protein C—see Table 1).…”
Section: Hcm: Morphomechanical Phenotypic Characteristicsmentioning
confidence: 99%
“…Here, we studied three disease causing missense mutations of the domain C1 that were recently identified in Egypt for the first time by Kassem et al, [12]. These HCM causing mutations: (i) Arg177His (ii) Ala216Thr and (iii) Glu258Lys are located in the strand-B, the D/E loop and the C-terminal of strand-G, respectively (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A mutational analysis study on an Egyptian cohort through Bibliotheca Alexandrina HCM (BA-HCM), a national programme showed that mutations in cardiac MyBP-C (cMyBP-C) gene are a common cause of HCM in Egypt [12]. More than 200 disease causing mutations have been reported in the cMyBP-C [7], [13][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation